TANTANGAN DAN STRATEGI PENERAPAN KURIKULUM TINGKAT SEKOLAH DASAR DI SEKOLAH LUAR BIASA - Huda, Fredella Khoirul; Putri, Nanda Aleydaaqika; Ardiana, Septia; Minsih, Minsih (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This research aims to identify and analyze challenges and formulate strategies in implementing elementary school curriculum in Special Education Schools (SLB). Using a qualitative approach with library research methods, this study examines various current literature sources regarding curriculum implementation in special education schools. The results show that the main challenges include gaps between the national curriculum and specific needs of students with special needs, limited teacher competency in curriculum adaptation, and suboptimal learning support infrastructure. Approximately 70% of special education schools experience difficulties in curriculum adaptation, while only 45% of teachers have comprehensive understanding of curriculum adaptation processes for children with special needs. Recommended optimization strategies include developing differentiation-based curriculum adaptation models, strengthening teacher professional development programs, and enhancing stakeholder collaboration. The implementation of these strategies requires a systematic approach and adaptive policy support to create a sustainable and quality special education ecosystem